Tissue Engineering: Cost and Time Effective Lithography of Reusable Millimeter Size Bone Tissue Replicas With Sub‐15 nm Feature Size on A Biocompatible Polymer (Adv. Funct. Mater. 19/2021). (10th May 2021) - Liu, Xiangyu; Zanut, Alessandra; Sladkova‐Faure, Martina; Xie, Liyuan; Weck, Marcus; Zheng, Xiaorui; Riedo, Elisa; de Peppo, Giuseppe Maria
Abstract : In article number 2008662, Elisa Riedo, Giuseppe Maria de Peppo, and co‐workers describe a novel thermochemi cal scanning probe lithography (tSPL)‐based platform for the low‐cost and high throughput fabrication of bone tissue replicas in a biocompatible material with nanoscale resolution. The bio‐tSPL platform creates unique opportunities for understanding the cell‐tissue microenvironment interactions and for applications in regenerative medicine, disease modeling, and drug screening.